SYNTHESIS N-PHENYLAMINEDITHIOCARBAMATE AS CHELATING AGENT IN SOLVENT EXTRACTION - Soja Siti Fatimah; Vera Musfiroh; Zackiyah Zackiyah; Husein H. Bahti; Iwan Hastiawan; Anna Permanasari (Chimica et Natura Acta, 2014)
Dithiocarbamate derivatives is a versatile ligand that contain two atoms of sulfur as a strong electrondonor. It combines with metals. N-phenylaminedithiocarbamate has synthesized and applied in solvent exctration. Synthesis carried out with addition carbon disulphide to N-phenylamine and concentrated pottasium hydroxyde in metanol. The result was characterized by spectroscopy 1H-NMR, 13C-NMR, FTIR, Elemental Analysis, that showed molecular structure was significant. Applied N-Phenylaminedithiocarbamate in solvent extraction showed precent of result Cu(II), Co(II), Cr(III) and Ni (II) were 90.45% - 99.99% at pH 4-9.